The influence of assuming and role-playing a false identity on event-related potentials. - Deck, Trevor Paul. (University of Ottawa (Canada), 2002)
Identity schemata serve to organize the content and regulate the processing of identity related information. The dissimulation of undercover agents and others has been associated with fundamental changes in the mental schemata and cognitive structures associated with their identity. This processing of identity information can be can be detected and quantified through Event Related Potentials (ERP). The purpose of the study was to compare the P300 ERPs in persons predisposed and not predisposed to dissociative experiences as they responded to factual (real) and counterfactual (false) personal identity information when asked to be themselves or dissimulate their real identity by adopting a false one. The interest was in examining whether information previously irrelevant to one's self-identity would be seen as meaningful when participants cognitively adopted a false identity and when they engaged in social-behavioural role-plays of that false identity. The degree to which the false identity was seen as meaningful was expected to vary as a function of scores on the Dissociative Experiences Scale (DES). Male students (19--24 yrs), 18 scoring high and 17 scoring low on the DES chose among three fabricated identities one they were to assume for the study. Eighty words representing their chosen false identity, their real identity, and two irrelevant identities served as stimulus items in a self-referencing task. ERP recordings from frontal, central, and parietal sites were obtained under four conditions. A pre-test of ERPs to all stimuli was followed by a second presentation where subjects assumed a false identity and denied their real identity. Subjects then participated in three semi-structured role-play interactions while assuming their false identity over a 3--5 day period. ERP recordings while assuming their false identity and again while assuming their real identity were subsequently obtained. P300 ERPs were elicited to real identity and to false identity information when subjects assumed one or the other. Importantly, previously obtained P300 responses to real identity stimuli were suppressed when ERPs to false identity stimuli were obtained. Role playing diminished P300 to a false identity. High, compared with low scoring, amnesia subjects of the DES were less able to suppress ERPs to their real identity when adopting a false identity. Results are discussed in relation to identity schema theory, dissociative disorders, with implications for undercover policing.
Keywords: Psychology, Behavioral.